Fay Hendrickson ([Kingston, Jamaica] : Planters' Punch, 1930)
Miss Fay Hendrickson, assistant in her father's business, [1930]
Keywords: Hendrikson, Fay; Chinese - Jamaica - History; Chinese - Jamaica